Biometry and conformation indexes in equipment competitors of boving in the Alagoan Semiarid - Joyce Ramos da Silva; Neilson SilvaSantos; Filipe Leal Augusto Dantas; Maria Telma de Aquino Rodrigues (Universidade Estadual de Alagoas, 2020)
Vaquejadais a sport spread throughout the Brazilian Northeast, the practice generates income for thousands of Brazilians and adds values in other activities. Thus, it is important to biometric analysis of animals that participate in this practice to define the morphometric parameters that directly impact the results of the animals. Aiming at such factors, the objective was to evaluate thebiometric characteristics of horses competing in vaquejada in the semiarid region of Alagoas. The research was carried out on the vaquejada track in the city of Olhod'Água do Casado. 44 animals were used, divided by sex. The hazel coat was the most expressive (96% frequency). The thoracic diameter and weight of females was higher than that of males with differences of 2.75 cm and 16.46 kg, respectively. Male horses showed greater height at the withers (152.94 cm) and croup (152.29 cm). The animals used invaquejadas in the Semi-arid Alagoan are predominantly of the Quarter Mile Breedand Azalã coat.